How Equal Temperament Ruined Harmony (and Why You Should Care) - Duffin, Ross W. (New York Norton, 2007)
Ross W. Duffin presents an engaging and elegantly reasoned exposé of musical temperament and its impact on the way in which we experience music. A historical narrative, a music theory lesson, and, above all, an impassioned letter to musicians and listeners everywhere, How Equal Temperament Ruined Harmony possesses the power to redefine the very nature of our interactions with music today.For nearly a century, equal temperament--the practice of dividing an octave into twelve equally proportioned half-steps--has held a virtual monopoly on the way in which instruments are tuned and played. In his new book, Duffin explains how we came to rely exclusively on equal temperament by charting the fascinating evolution of tuning through the ages. Along the way, he challenges the widely held belief that equal temperament is a perfect, "naturally selected" musical system, and proposes a radical reevaluation of how we play and hear music.
Shouldn't leading notes lead? -- How temperament started -- Non-keyboard tuning -- "How long, O Lord, how long?" -- A bridge to the nineteenth century -- Really better or simply easier? -- Some are more equal than others -- The "Joachim mode" -- "The limbo of that which is disregarded" -- Where do we go from here?
Includes bibliographical references (p. 171-175) and index.
Keywords: Temperament